Asian and Pentecostal : The Charismatic Face of Christianity in Asia Revised Edition - Anderson, Allan; Tang, Edmond (Book collections on Project MUSE., 2011)
This book provides a thematic discussion and pioneering case studies on the history and development of Pentecostal and Charismatic churches in the countries of South Asia, South East Asia, and East Asia.